2019
DOI: 10.1093/mnras/stz1305
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circumstellar helium in Type Iax progenitor systems

Abstract: We present direct spectroscopic modeling of 44 Type Iax supernovae (SNe Iax) using spectral synthesis code SYNAPPS. We confirm detections of helium emission in the earlytime spectra of two SNe Iax: SNe 2004cs and 2007J. These He i features are better fit by a pure-emission Gaussian than by a P-Cygni profile, indicating that the helium emission originates from the circumstellar environment rather than the SN ejecta. Based on the modeling of the remaining 42 SNe Iax, we find no obvious helium features in other S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 77 publications
4
20
0
Order By: Relevance
“…Among the group of faint and fast objects, SN2005ek (Drout et al 2013), SN2010X (Kasliwal et al 2010), as well as some of the calcium-rich gap transients including PTF10iuv (Kasliwal et al 2012), iPTF16hgs (De et al 2018b), and SN2019ehk (Jacobson-Galán et al 2020;Nakaoka et al 2020) have been suggested as good candidates for ultra-stripped SNe (Moriya et al 2017). However, properties of these objects are also consistent with alternative interpretations, including corecollapse of stars with extended hydrogen-free envelopes (Kleiser & Kasen 2014;Kleiser et al 2018aKleiser et al , 2018b, and explosive detonation of a helium shell on the surface of white dwarfs (Shen et al 2010;Sim et al 2012;Jacobson-Galán et al 2019;Polin et al 2019;.…”
Section: Introductionmentioning
confidence: 81%
“…Among the group of faint and fast objects, SN2005ek (Drout et al 2013), SN2010X (Kasliwal et al 2010), as well as some of the calcium-rich gap transients including PTF10iuv (Kasliwal et al 2012), iPTF16hgs (De et al 2018b), and SN2019ehk (Jacobson-Galán et al 2020;Nakaoka et al 2020) have been suggested as good candidates for ultra-stripped SNe (Moriya et al 2017). However, properties of these objects are also consistent with alternative interpretations, including corecollapse of stars with extended hydrogen-free envelopes (Kleiser & Kasen 2014;Kleiser et al 2018aKleiser et al , 2018b, and explosive detonation of a helium shell on the surface of white dwarfs (Shen et al 2010;Sim et al 2012;Jacobson-Galán et al 2019;Polin et al 2019;.…”
Section: Introductionmentioning
confidence: 81%
“…The model of SNe Iax originating from WD-He star systems is supported by the generally young ages of SNe Iax environments (Lyman et al 2018;Takaro et al 2020), though at least one SN Iax exploded in an elliptical galaxy (Foley et al 2010a). The detection of helium is also reported in the spectra of SNe 2004cs and 2007J (Foley et al 2013;Jacobson-Galán et al 2019;Magee et al 2019), but there is a debate on the real nature of these two objects (see White et al 2015;Foley et al 2016). Moreover, the apparent lack of helium in the majority of known SNe Iax (Magee et al 2019) shows the necessity of further investigation of this point.…”
mentioning
confidence: 92%
“…However, a stripped mass of ≈ 3×10 −4 M was found in the simulation of Zeng et al (2020) who assumed a weak pure deflagration model. We also note that a limit of 2 × 10 −3 M is found for stripped H in SNe Iax (Jacobson-Galán et al 2019).…”
Section: Discussionmentioning
confidence: 51%